2002
DOI: 10.1093/fampra/19.3.251
|View full text |Cite
|
Sign up to set email alerts
|

A short-term intervention in a multidisciplinary referral clinic for primary care frequent attenders: description of the model, patient characteristics and their use of medical resources

Abstract: The integrated approach of the clinic satisfied at least three needs: of the patient, of the referring physician and of the health maintenance organization. The results of this uncontrolled pilot study suggest that this intervention helped to modify illness behaviour, decreasing the costs of medical investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 10 publications
4
42
0
5
Order By: Relevance
“…The 7H+T intervention has been developed over time [11][12][13][14] and is based on the experience of JA Bellón since 1998. Different versions of the workshop have been given around Spain.…”
Section: The '7 Hypothesis + Team' Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 7H+T intervention has been developed over time [11][12][13][14] and is based on the experience of JA Bellón since 1998. Different versions of the workshop have been given around Spain.…”
Section: The '7 Hypothesis + Team' Interventionmentioning
confidence: 99%
“…10 A common underlying assumption is that if health problems are improved, the need to consult decreases, although findings to support this have been both negative 4,5 and positive. [6][7][8][9][10] Another group of intervention studies [11][12][13][14][15][16] used a comprehensive focus with multi-component interventions, although results were inconclusive, and the interventions tended to be unsuccessful; also, most of these studies had methodological problems. O'Dowd intervened successfully in 'heartsink' patients, most of whom are frequent attenders, although no control group was involved.…”
Section: Introductionmentioning
confidence: 99%
“…2,10,13 Patients with MUPS often -but not always -have symptoms of anxiety and depression: so-called 'somatisation'. 9,14,15 Research has shown that, although a number of patient-focused psychological and behavioural interventions are potentially effective for people with somatisation disorders, they are often unacceptable to these patients. [16][17][18][19] Other interventions have focused on the doctor-patient communication in everyday consultations, and Morriss et al demonstrated that GP training in the use of their 'reattribution model' is beneficial, but of limited acceptability to GPs.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12] Intervention studies have often focused on people with both medically unexplained symptoms and anxiety and depression ('somatisers'), a combination that constitutes about 40% of the group overall. 13,14 These studies include the work of Morriss and colleagues, [15][16][17] who have developed and tested a 'reattribution model' for use by GPs, as well as evaluations of a wide range of approaches directed at the patients, including medication, patient education, cognitive-behavioural therapy (CBT), and counselling. [18][19][20][21] These approaches have been shown to be effective for some patients but to be limited by low acceptability among both GPs and patients.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] These approaches have been shown to be effective for some patients but to be limited by low acceptability among both GPs and patients. Other complex interventions that pragmatic trials have shown to have some benefits for people with unexplained symptoms, whether or not they have anxiety and/or depression, include exercise training, 6 multidisciplinary clinics, 13 and nurse practitioner clinics aimed at improving social and communication skills and rationalising medication. 22 These resources are, however, rarely available.…”
Section: Introductionmentioning
confidence: 99%